La notion de bail professionnel en droit OHADA et ses implications sur la théorie générale du fonds de commerce - André Desmonds Eyango Djombi (Juridical Tribune, 2016)
The last reform of the Uniform Act on General Commercial Law OHADA reconsidered several pieces of commercial law. The concept of leasing has not been spared. She, who was accompanied by the "commercial" substantive, has been transformed into "commercial lease". Question of style or simple semantics? Certainly not, because the legislature in 1997, had not previously dared revise the designation commercial lease that no longer fit with the extension of the beneficiaries he had devoted himself. With the reform of December 2010, the institution of the lease has just renamed. Parliament also confirmed the extension of the scope of economic actors involved in the protection of the lease. The regime of former Uniform Act was therefore not fully extended, particularly since we noted another significant change in the new text. Contrary to former Article 69 which devoted two cumulative criteria necessary for the implementation of the lease of the regime, including the situation in a populated city of more than 5,000 people and membership of local under lease to a designated class, the new text retains a single criterion, that of belonging to a local specific category. This mutation disrupts some basics of goodwill theory. Indeed, with the increasing scope of lessees, there is a sliding protection to professional trader. This causes result in a substitution of the lease of the foundation that passes from customer to the profession. The loss of the privileged place of business customers coupled with doctrinal and jurisprudential developments in the theory of civil customers, argue for an assimilation of the different customer categories.